Pengaruh Self Assessment System, Teknologi Informasi, dan Pemahaman Perpajakan terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi di Tangerang Raya - Nicholas Nathan Santoso; Angeliny Angeliny; Florencia Irena Lawita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of the Self-Assessment System, information technology utilization, and tax knowledge on the compliance level of individual taxpayers in the Greater Tangerang area. Tax compliance plays a crucial role in supporting state revenue, especially in the current era of digitalized tax systems. A quantitative approach was employed using a survey method through the distribution of questionnaires. The sampling technique used was purposive sampling, targeting individual taxpayers who are registered and actively report their taxes. The collected data were analyzed using SPSS version 26, including tests for validity, reliability, classical assumptions, and multiple linear regression analysis. The results indicate that the Self-Assessment System, information technology, and tax knowledge have a positive and significant influence on taxpayer compliance. These findings reinforce the importance of regulatory understanding, accessible electronic systems, and active taxpayer participation in fulfilling tax obligations independently. This research is expected to serve as a reference for tax authorities in formulating more effective strategies to increase taxpayer compliance through education and improvements in digital tax systems.